The Effect Of English Video Podcast For Developing Students’ English Skill In Listening Comprehension - Engelina Salainti P.; Sukardi Weda; Andi Hamzah Fansury (Jounal of Primary Education, 2023)
Teaching and learning process in the classroom will run well when the learning process uses the good method. One of the method that can be applied in the classroom is using technology such as podcast. The aim of this research is to discover the effectiveness of using English Video Podcast in improving the students’ listening comprehension of eight-ninth students of SMP Advent Makassar. This research is applied by using a mix method approach, specifically the researcher applied quasi-experimental research design, and the data analysis was done by statistical description. And the based on the researcher findings, the use of English video podcast can be effective learning media to improve students’ listening comprehension. It can be seen there was increasing from the data of Pre-Test to the Post-test after the teacher gave the treatment to the experimental group. Before the treatment was given the students’ mean score for the experimental group on the pre test is 56.50 and after the treatment was given the students’ mean score is 78.50. It means that the using of podcast has improved students’ listening comprehension. The result was improved. It is supported by some previous study that also has a positive effect by using a podcast in teaching listening. And based on the questionnaire and the interview given the result showed positive impact of using English video podcast in improving listening comprehension.